2017
DOI: 10.1007/s00056-016-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and histomorphometric evaluation of bone regeneration using nanocrystalline hydroxyapatite and human freeze-dried bone graft

Abstract: Based on the results of this experimental study, both NanoBone and FDBG exhibited a similar effect on bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
3
7
3
Order By: Relevance
“…Autogenous grafts integrate faster, and the volume of bone seen for SS and MS groups at 2 months was seen within one month for particulate autogenous graft in one study. 28 However the values obtained in this study were slightly lower and higher to those observed by Takauti 29 (78%) and Sadeghi 30 (23%) in rabbits at 2 and 3 months for ceramics and nano-hydroxyapatite respectively. The possibility of thermal damage to the material appears remote in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…Autogenous grafts integrate faster, and the volume of bone seen for SS and MS groups at 2 months was seen within one month for particulate autogenous graft in one study. 28 However the values obtained in this study were slightly lower and higher to those observed by Takauti 29 (78%) and Sadeghi 30 (23%) in rabbits at 2 and 3 months for ceramics and nano-hydroxyapatite respectively. The possibility of thermal damage to the material appears remote in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…Compared with the traditional HA, nanohydroxyapatite (nHA) has a larger surface area and better bioactivity and loading capacity. There were sufficient preclinical and clinical findings to support the osteogenic effect of nHA in tissue engineering (Shirmohammadi et al, 2014;Kamboj et al, 2016;Dayashankar et al, 2017;Sadeghi et al, 2017). Chitosan has been used for periodontal treatments in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…The field of nanotechnology can be applied to scaffolds such as HA to create nHA, which was shown to enhance bone regeneration and to accelerate healing after sinus augmentation [60]. In fact, nHA displayed similar effects in bone regeneration compared to freeze dried bone allografts in a rabbit model [63]. In addition, nHA used in the augmentation of extraction sockets was shown to reduce the degree of gingival invaginations [64].…”
Section: Bone Regeneration For Dental Implants and Mandibular Defectsmentioning
confidence: 99%